PELATIHAN APLIKASI QUIZIZZ UNTUK MENINGKATKAN KOMPETENSI GURU DALAM PEMBELAJARAN INTERAKTIF SDN 3 TAMPIALA - Nurhasanah; Ikbal Ikbal; Silfina; Moh Salim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
The Quizizz application training at SDN 3 Tampiala was conducted as an effort to improve teacher competency in integrating digital technology into interactive learning. The background of this activity was the still limited use of technology-based learning media by teachers, who tended to use conventional methods such as lectures and written assignments, resulting in less than optimal student engagement. Through this training, teachers were equipped with practical skills in creating quiz-based questions, setting game modes, using leaderboard features and instant feedback, and analyzing student learning outcomes more quickly and efficiently. The implementation results showed an increase in teacher competency both in terms of technical skills and creativity in designing learning. In addition, this training had a positive impact on increasing student learning motivation because the learning environment became more enjoyable and interactive. However, several obstacles such as limited internet connection and differences in teachers' initial abilities in using digital devices still remain obstacles that need to be addressed. Overall, this training successfully became the first step in supporting digital transformation in education, as well as providing alternative learning methods relevant to the needs of 21st-century students.